(untitled) (Global Journal of Science Frontier Research, 2013)
Background and Objective : A number of studies have previously described elevated levels of homocysteine as an independent coronary heart disease and stroke risk factor. The results of above studies show different data for the methylenetetrahydrofolate reductase (MTHFR) genetic polymorphism and hyperhomocysteinemia, which is the cause of cerebrovascular accident. Purpose of the study was to determine whether there is a link between hyperhomocysteinemia and A1298CC, C677 genotype associated with acute cerebral infarction. Methods : The prospective study included patients (n=102) with acute cerebral infarction, regardless of its genesis or transient ischemic attack, and patients with a history of cerebral infarction of any age, that correlates with the imaging techniques. The control group (n = 34) consisted of patients without a history of cerebrovascular disease, showing no indication of previous strokes according to imaging techniques. Homocysteine was determined using IMMULITE 2000 testing system. Results : Comparing the both groups, increased homocysteine level association with the cerebrovascular event was not observed (p=0.4). By studying the genetic polymorphism of MTHFR, a statistically significant relationship of elevated homocysteine with C677TT (p=0.15), C677CT (p=0.61) and C677CC (p=0.90) was not detected. Similar results were obtained for A1298 genetic polymorphism. Conclusion : This study showed that there is no link between hyperhomocysteinemia and MTHFR genetic polymorphism in the investigated population associated with risk of acute cerebral infarction. Taking into consideration the relationship of homocysteine with folic acid and vitamin B12 levels, the next phase of study will include the determination of these two parameters in addition.